The Determinant Analysis Of Socio Economic Status To Accounting Learning Outcome In Upi “Yptk” College Students - Susy Yuliastanty (Jurnal Ilmiah Pendidikan Scholastic, 2017)
This study aims to analyze (1) the influence of head of household education on accounting learning outcomes, (2) the influence of family head work on accounting learning outcomes, (3) the influence of head of household income on accounting learning outcomes, (4) the influence of family demographics on learning outcomes Accounting (5) the influence of the environment on the learning outcomes of accounting, (6) the influence of internal characteristics of children on the learning outcomes of accounting, (7) the influence of children's gender on accounting learning outcomes, (8) the influence of head of family education, Family demographics, environment, internal characteristics of children and child gender on accounting learning outcomes. This research type is descriptive associative, where population of this research is all student of UPI "YPTK" majoring in Accountancy, the sample in this research amounted to 247 students taken with multistage random sampling technique. Hypothesis test using F test and t test with α = 0.05. The result of the research shows that (1) the education of the head of household has a significant and positive effect on the learning result of accounting (2) the parent's job has a significant and positive effect on the learning result of accounting, (3) the income of the head of family has a significant and positive influence on the learning result of accounting, 4) family demography has significant and negative effect on accounting learning result, (5) environment has significant and negative effect on accounting learning result, (6) internal characteristic of children has significant and positive effect on accounting learning result, (7) child gender has significant effect on result Learning accounting, (8) family head education, family head work, family head's income, family demography, environment, internal characteristics of children and children's gender have a significant effect on accounting learning outcomes.